Uganda : Second Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2008)
Uganda's medium-term expenditure framework (MTEF) aims at higher public savings based on spending restraint and rising domestic revenue. The Bank of Uganda (BOU) has successfully contained the one-time shocks to prices of increases in electricity tariffs and temporary sugar and diesel fuel shortages. In an environment of strong inflows, price stability remains the primary objective of monetary policy. A shallow financial sector limits Uganda's ability to absorb foreign exchange inflows and is in itself a formidable obstacle to faster economic growth.